2011
DOI: 10.1093/humrep/der163
|View full text |Cite
|
Sign up to set email alerts
|

Repeated ovarian stimulation with corifollitropin alfa in patients in a GnRH antagonist protocol: no concern for immunogenicity

Abstract: BACKGROUNDOne injection of corifollitropin alfa replaces the first seven daily FSH injections in controlled ovarian stimulation (COS) cycles. Repeated treatment with therapeutic proteins may cause immune responses or hypersensitivity reactions. We assessed the immunogenicity and safety of corifollitropin alfa treatment in up to three COS cycles.METHODSIn this multicentre, phase III uncontrolled trial, patients (>60 kg) started treatment with one injection of 150 µg corifollitropin alfa on cycle Day 2 or 3 of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
0
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 23 publications
(32 reference statements)
2
45
0
6
Order By: Relevance
“…The optimal corifollitropin dose has been calculated to be 100 mg for women with a body weight %60 kg and 150 mg for women with a body weight >60 kg (8,9) From phase II and III studies it was concluded that a single injection of corifollitropin alfa can replace the first seven injections with standard daily gonadotropins and that stimulation can be continued with daily FSH injections if the need arises (9). This makes corifollitropin alfa potentially more patient-friendly and may lead to a lower dropout rate of patients (10), if safety and effectiveness are first demonstrated. The present review summarizes the evidence from randomized controlled studies (RCTs) on effectiveness, safety, and tolerance of corifollitropin alfa and rFSH, in IVF or ICSI cycles.…”
mentioning
confidence: 99%
“…The optimal corifollitropin dose has been calculated to be 100 mg for women with a body weight %60 kg and 150 mg for women with a body weight >60 kg (8,9) From phase II and III studies it was concluded that a single injection of corifollitropin alfa can replace the first seven injections with standard daily gonadotropins and that stimulation can be continued with daily FSH injections if the need arises (9). This makes corifollitropin alfa potentially more patient-friendly and may lead to a lower dropout rate of patients (10), if safety and effectiveness are first demonstrated. The present review summarizes the evidence from randomized controlled studies (RCTs) on effectiveness, safety, and tolerance of corifollitropin alfa and rFSH, in IVF or ICSI cycles.…”
mentioning
confidence: 99%
“…As far as safety is concerned, the pooled analysis of three large clinical trials (12,13,28) showed that the incidence of severe OHSS was consistent with that expected in the relatively young patient population and was similar for patients receiving CFα (1.8 %) or daily rFSH (1.3 %) (26). In a recent pilot study comparing CFα given on day 2 vs. day 4 in young expected normal responders, the proportion of patients with more than 20 follicles >11 mm diameter the day of ovulation trigger was found to be higher in the day 4 group, raising the suspect that day 4 administration could be associated with a higher risk of OHSS (4).…”
Section: Discussionmentioning
confidence: 99%
“…Согласно имеющимся на сегодня данным, до 4 инъекций 15 мкг корифоллитро-пина альфа у мужчин с гипогонадотропным гипогонадиз- Первоначально вероятность иммуногенных реакций на повторные введения корифоллитропина альфа, с учетом молекулярной структуры и степени очистки, оценивалась как незначительная. Однако с целью оценки иммуноген-ности корифоллитропина альфа было проведено крупное открытое многоцентровое клиническое неконтролируе-мое исследование Trust [17]. В исследование было включе-но 30 медицинских центров.…”
Section: ключевые словаunclassified
“…Все образцы, кроме одного, полученного после 2-го цикла, были отрицатель-ными [17]. В последнем было выявлено значимое усиле-ние связывания (р < 0,05) в антительном тесте, истощае-мое при внесении корифоллитропина альфа и рФСГ, но не ЛГ или ХГЧ.…”
Section: ключевые словаunclassified
See 1 more Smart Citation